Keanekaragaman Jenis Serangga Pada Beberapa Varietas Jagung Hibrida dan Jagung Transgenik - Selamat Ariyanto Gulö; Darma Bakti; Fatimah Zahara (Jurnal Agroekoteknologi, 2014)
The objective of this research was to studythe abundance and diversity of insects on corn hybrid andtransgenic variety. It was conducted at Balai Benih Induk Tanaman Palawija Tanjung Selamat landarea dan Pest Laboratory, Facultyof Agriculture, University of North Sumatra, Medan started onMarch 2013 until Juli 2013. This research used 3 kinds of insect traps (Sweep Net, PitfallTrap,Yellow Sticky Trap), and six study replications. The first treatment varieties planted PRG NKC7-603 are sprayed with Glyphosate, the second treatment varieties PRG NK C7-603 are weededmanually, the third treatments varieties C7 were weeded manually, and the fourth treatmentvarieties DK979 were weeded manually.The result showed that insect caughthas consisting of 9Ordo and 49families. The highest relative density values on PRG C7 NK-603 (application ofglyphosate) was 16,5 % and the lowest was 0,136 %. The highest relative density values on PRGC7 NK-603 was 16,16 % and the lowest was 0,116 %. The highest relative density values on C7was 17,114 % and the lowest was 0,0781 %. The highest relative density values on DK979 was18,4 % and the lowest was 0,138 %.Shanon-Weiner (H’) index diversity of insect on PRG C7 NK-603 (applicationof glyphosate) was 3,2636, on PRG C7 NK-603 was 3,2407, on C7 was 3,1834,and on DK979was 3,144.All varieties has a high diversity and ecosystem stability.Key words : Diversity, Insect, Corn